رتبة الميلاد النفسية مفهوم مركزي في العلاج النفسي الفردي - خـالد, خـياط (Sciences humaines; Vol. 37 (2014): SCIENCES HUMAINES(Novembre))
يعد الاصطلاح الأدلري "رتبة الميلاد النفسية" من المفاهيم المركزية التي يبحث عنها المعالج النفسي الأدلري خلال عملية العلاج، سواء كان فرديا أو جمعيا أو زوجيا أو أسريا. لاحظ أدلر وجود تكرارات لخصائص معينة لدى أفراد أسر مختلفة، تشيع لدى الأطفال ذوي رتبة الميلاد نفسها. وقد وضح أدلر أن مفهوم رتبة الميلاد النفسية لا يتمثل في ترتيب الولادة الزمني، بل بالوضعية التي يجد الطفل نفسه فيها ضمن تشكيلة الأسرة. وقد حدد لكل وضعية ميلاد مجموعة من الخصائص المحتملة . غير أنها ليست صفات حتمية، بل وجودها خاضع للعديد من المتغيرات الإضافية التي قد تنقل الطفل من رتبة ميلاد متوقعة إلى رتبة ميلاد نفسية غير متطابقة مع ترتيبه التسلسلي في تشكيلة الأسرة.   The Adlerian term " psychological Birth order " is a central concept adlerian therapist are looking for in the treatment process , whether an individual, a group or a family therapy . Adler observed the occurrence of certain characteristics among children of different families , common among children with birth rank . Adler had clarified that the concept of psychological Birth order is not synonim of chronological rank of birth , but the position where the child finds himself in the family constelation . Adler has identified for each birth position a set of probable characteristics. However, it is not a matter of determinism. Adlerians believe that the presence of these characteristics deponds on a number of additional variables that may change the child from his birth rank to an unexpected psychological birth order.